2023
DOI: 10.3390/nu15030695
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Preventing and Treating Vitamin D Deficiency: A 2023 Update in Poland

Abstract: Introduction: All epidemiological studies suggest that vitamin D deficiency is prevalent among the Polish general population. Since vitamin D deficiency was shown to be among the risk factors for many diseases and for all-cause mortality, concern about this problem led us to update the previous Polish recommendations. Methods: After reviewing the epidemiological evidence, case-control studies and randomized control trials (RCTs), a Polish multidisciplinary group formulated questions on the recommendations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
18

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(141 citation statements)
references
References 81 publications
0
123
0
18
Order By: Relevance
“…Although vitamin D toxicity is a very rare case, it can occur when an excess of supplements is taken (for values > 100 ng/mL–250 nmol/L, not achievable with sunlight exposure or regular food intake, but generally as a consequence of the unintentional assumption of extremely high doses) [ 203 ]. In any case, it is important that patients and physicians are conscious that this event can occur, requiring revision of the supplementation (e.g., reduction or cessation) until target 25(OH)D concentration is achieved again [ 204 ].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Although vitamin D toxicity is a very rare case, it can occur when an excess of supplements is taken (for values > 100 ng/mL–250 nmol/L, not achievable with sunlight exposure or regular food intake, but generally as a consequence of the unintentional assumption of extremely high doses) [ 203 ]. In any case, it is important that patients and physicians are conscious that this event can occur, requiring revision of the supplementation (e.g., reduction or cessation) until target 25(OH)D concentration is achieved again [ 204 ].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Nevertheless, we aimed to include the best available evidence up to 11 February 2023 to provide guidance for developing public health measures to reduce the health burden of vitamin D deficiency in KSA and the UAE, because substantial reductions in adverse health outcomes in Saudi Arabia and the UAE are likely to be achieved by raising the minimum serum 25(OH)D concentration to above 30 ng/mL. The U.S. Endocrine Society [ 4 ] and the consensus from vitamin D conferences in Poland [ 29 , 262 ] recommend daily intakes up to 2000 IU/d vitamin D 3 , while reviews from the U.S. Institute of Medicine in 2011 [ 3 ] and from the UK both demonstrate, and affirm, that 4000 IU/d is safe and results in greater health benefits. Food fortification with vitamin D can be effective, using a variety of foods including fats, dairy produce, and flour-based products [ 263 , 264 ] though supplementation is usually required in addition for those at high risk of deficiency such as the elderly, those with indoor life styles, shift workers, pregnant women, the obese, diabetics, dark-skinned individuals [ 255 , 265 ], and vegan/vegetarians [ 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the effects of the large prospective intervention study CORONAVIT (phase 3, open-label, randomized controlled trial) conducted in the UK, which showed that the supplementation of vitamin D in subjects with suboptimal vitamin D status (<30 ng/mL; n = 2674) increased 25OHD concentrations; however, this was not associated with protection against COVID-19 [ 16 ]. Our results are also in keeping with the results of the metanalysis by Wang et al [ 17 ], where the authors, analyzing data from 16 studies (2756 patients), confirmed increased mortality, and an increased likelihood of hospital admissions and longer hospital stay, particularly in patients with more severe 25OHD deficiency (12 ng/mL cut-off was applied in seven studies, 20 ng/mL cut-off in eight studies, 25 ng/mL cut-off in one study, while a 30 ng/mL cut-off [ 13 , 14 ] was never applied). It should be noted, however, that several studies, e.g., [ 18 , 19 , 20 ], analyzed 25OHD in either hospitalized or symptomatic patients with COVID-19 infection, where these concentrations were indeed lower than in the general population or in age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…25OHD sufficiency cut-offs were defined as 25OHD >20 ng/mL (50 nmol/L) [ 12 ] or as 25OHD > 30 ng/mL (75 nmol/L) [ 13 , 14 ]. The issue of whether a 20 ng/mL or 30 ng/mL cut-off should be applied for the Polish population was discussed in our previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%